Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd003992.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus intravenous antibiotic treatment for febrile neutropenia in cancer patients

Abstract: Based on the present data, oral treatment is an acceptable alternative to intravenous antibiotic treatment in febrile neutropenic cancer patients (excluding patients with acute leukaemia) who are haemodynamically stable, without organ failure, not having pneumonia, infection of a central line or a severe soft-tissue infection. The wide confidence interval for mortality allows the present use of oral treatment in groups of patients with an expected low risk for mortality, and further research should be aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 69 publications
0
22
0
1
Order By: Relevance
“…Identification of patients suitable for outpatient management is crucial since this cost-effective strategy allows savings, limits the risk of hospital-acquired infections and improves the patients' quality of life [36,37]. FN patients with a MASCC score ≥ 21 and without other clinical warning signs can be safely managed in the outpatient setting if they are able to take oral medication and have a committed caregiver [38,39]. Successful management of CIN in BC outpatients requires the patients and their caregivers to be educated to rapidly recognize signs and symptoms of possible infection.…”
Section: Management Of Febrile Neutropeniamentioning
confidence: 99%
“…Identification of patients suitable for outpatient management is crucial since this cost-effective strategy allows savings, limits the risk of hospital-acquired infections and improves the patients' quality of life [36,37]. FN patients with a MASCC score ≥ 21 and without other clinical warning signs can be safely managed in the outpatient setting if they are able to take oral medication and have a committed caregiver [38,39]. Successful management of CIN in BC outpatients requires the patients and their caregivers to be educated to rapidly recognize signs and symptoms of possible infection.…”
Section: Management Of Febrile Neutropeniamentioning
confidence: 99%
“…The primary reasons for combination therapy are to prevent the development of resistance, improve outcomes, provide synergy, and provide sufficient antibiotic coverage should the pathogen be resistant to the agent that would have been chosen as single therapy. The former two arguments, while logical, have yet to be proven (36,209). In fact, a meta-analysis suggested that clinical failure was more common with combination therapy, as was nephrotoxicity; aminoglycosides were the second agent, and combination therapy did not prevent new resistance patterns (209).…”
Section: Antibiotic Managementmentioning
confidence: 99%
“…The former two arguments, while logical, have yet to be proven (36,209). In fact, a meta-analysis suggested that clinical failure was more common with combination therapy, as was nephrotoxicity; aminoglycosides were the second agent, and combination therapy did not prevent new resistance patterns (209). However, given that mortality is higher when therapy is inappropriate during the first 48 h, we favor initiating combination therapy for patients at risk for multidrug-resistant organisms until sensitivities are known.…”
Section: Antibiotic Managementmentioning
confidence: 99%
“…[4,5] Evidence shows that some pediatric patients with cancer who develop FN could be treated as outpatients or have an early discharge or even be treated as an outpatient. [6][7][8] Adoption of these practices would require institution specific systems to be in place for risk stratification and outpatient monitoring, with consideration for patient travel and social circumstances. [9] Evaluation of the impact of FN on health care utilization in the United States (US) could lead to improved insight into both hospital-and patient-level factors that impact length of stay.…”
Section: Introductionmentioning
confidence: 99%